The Impact of Gender Composition on Board of Director, Commissioner, Director, CEO and Ownership Structures on Dividend Payment Decisions in Indonesia: Agency Theory & Stewardship Theory - maimun, Tuti Zakiyah; Wahyuni windasari (Universitas Muhammadiyah Prof. DR HAMKA., 2025)
This study examines the influence of several board composition variables and ownership structure on dividend payment policies with a more Agency Theory & Stewardship Theory approach. Sampling using the purposive sampling method in IDX-listed manufacturing companies in 2020-2023. The sample of this study was 445 samples. The data analysis method used is panel regression analysis with independent variables of Dividend Policy and dependent variables, namely the Gender Composition of the Board of Directors, the Gender Composition of the Board of Commissioners, the Female Director, the Female Independent Director, the Female Executive Director, the Female CEO, the Capital Structure. The application used is the STATA 17 application. The effect of the composition of the female board of directors, the composition of the female board of commissioners, and the composition of ownership on dividend policy in this study resulted in a significant positive effect. It supports the existence of stewardship theory. Meanwhile, the influence of female executive directors on dividend policy in this study has no effect. The results are significantly negative for the Effect of Women CEOs on dividend policy in this study.